2009
DOI: 10.1143/jjap.48.08jb17
|View full text |Cite
|
Sign up to set email alerts
|

Power-Law Stress and Creep Relaxations of Single Cells Measured by Colloidal Probe Atomic Force Microscopy

Abstract: We measured stress and creep relaxations of mouse fibroblast cells arranged and cultured on a microarray, by colloidal probe atomic force microscopy (AFM) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…The above results show that presence of proteins in the medium also affects probe-cell adhesion, which may be connected with endocytosis-associated or receptor-ligand binding events on the cell surface. It was shown that probe hydrophobization can decrease adhesion to the cell surface [9], but not completely, and this effect can be cell specific [59]. Overall, cell adhesion is a very specific matter and can be affected by cell type, probe material, medium composition and other parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above results show that presence of proteins in the medium also affects probe-cell adhesion, which may be connected with endocytosis-associated or receptor-ligand binding events on the cell surface. It was shown that probe hydrophobization can decrease adhesion to the cell surface [9], but not completely, and this effect can be cell specific [59]. Overall, cell adhesion is a very specific matter and can be affected by cell type, probe material, medium composition and other parameters.…”
Section: Discussionmentioning
confidence: 99%
“…6C). Indeed, for the PAA gels, force relaxation can be roughly described by single exponential decay in accordance with the standard linear solid model [41], while for cells the power law decay model is more appropriate [9,42,43]. The associated increase in the indentation depth and contact area due to the decrease in cantilever deflection achieved ≈6%, which may contribute to the increase in F ad .…”
Section: Vero Cells In L-15 Mediummentioning
confidence: 90%
See 1 more Smart Citation
“…Rheological properties of single cells have been investigated in the time domain with creep 23,24 and stress relaxation [25][26][27] experiments. Those techniques were used recently to map the relaxation behavior of single cells.…”
mentioning
confidence: 99%
“…This suffers from the precise estimate of the Newtonian viscous damping coefficient l in the power-law rheology. 17 Also, to optimize the mapping time, a longer relaxation process exhibiting a power-law behavior 24 is difficult to be measured. 28,29 Those limits mentioned above are not imposed on frequency domain measurements.…”
mentioning
confidence: 99%